A 10-Year-Old Girl’s Dysfunctional ‘Self-Help’ in ADHD: Suppression of Hyperkinetic Symptoms via Self-Induced Weight Loss in the Context of Anorexia Nervosa—A Case Report - Mestermann, Stefan; Stonawski, Valeska; Böhm, Lea; Kratz, Oliver; Moll, Gunther; Horndasch, Stefanie (Children, 2023)
Anorexia Nervosa (AN) and Attention Deficit Hyperactivity Disorder (ADHD) are frequent mental disorders in child and adolescent psychiatry. Comorbidity of these disorders is, however, rare among minors. Thus, little is known about their mutual impact on illness development as well as diagnostic and therapeutic influencing factors. We report the case of a 10-year old girl with AN and massive underweight. At the age of 5, ADHD had been diagnosed. Application of ADHD-specific medication had been refused by her caregiver. As of 3rd grade, hyperkinetic symptoms were significantly reduced, which was later linked to beginning AN-induced weight loss. At inpatient admission, no clinically relevant ADHD-related symptoms were present. Accompanying weight gain, rather ‘sudden’ appearance of attention difficulties, motoric hyperactivity and impulsivity were reported, widely impairing our patient’s schoolwork and further daily life. Methylphenidate medication showed good clinical response and tolerability. We hypothesize that the former massive underweight had suppressed ADHD-specific behaviour. AN with significant weight loss could possibly mask hyperkinetic symptoms in children. Thus, sufficient clinical diagnostics and intense monitoring during ED treatment are required. Physicians and therapists should be sensitized for interactions in the joint occurrence of these mental disorders among minors.
CRIS-Team Scopus Importer:2023-10-06
Keywords: ADHD; anorexia nervosa; child and adolescent psychiatry; comorbidity; mental health; methylphenidate; weight loss

Ex vivo glucocorticoid receptor-mediated IL-10 response predicts the course of depression severity - von Zimmermann, Claudia; Böhm, Lea; Richter-Schmidinger, Tanja; Kornhuber, Johannes; Lenz, Bernd; Mühle, Christiane (Journal of Neural Transmission, 2021)
Directly measuring hypothalamic pituitary adrenal (HPA) axis function, an important player in affective disorders, is intensive and invasive. A crucial component of this system, the activity of the glucocorticoid receptor (GR), can be assessed ex vivo instead. Here, we investigated GR sensitivity in patients with major depressive disorder (MDD) to determine its predictive potential. Psychometric data and blood samples were collected from patients experiencing a major depressive episode (MDE, n = 87), healthy control subjects (n = 49), and patients with remitted MDD (n = 31) at baseline and (for patients) after median 20 days of follow-up after treatment as usual. Blood cells were stimulated ex vivo with lipopolysaccharide and the effect was suppressed by increasing dexamethasone (DEX) concentrations. The resultant cytokine secretion profile (for IL-6, IL-10, and TNF-α) was considered indicative of GR activity. Higher baseline scores of the Montgomery–Åsberg Depression Rating Scale (MADRS) were associated with a stronger decrease of logIC IL-6 (indicating an increase of GR sensitivity). Higher baseline logEC IL-10 (indicating a lower GR sensitivity) and a stronger reduction of logEC IL-10 (indicating a stronger increase in GR sensitivity) were associated with a stronger decrease in the MADRS score. Patients with remitted MDD showed higher logIC TNF-α values (indicating lower GR sensitivity) in comparison to patients with a current MDD at baseline and follow-up. Initially low GR sensitivity measured ex vivo in peripheral blood cells that increases over the course of treatment could serve as a predictive marker for stronger improvement in depression severity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Cytokines; Depression; Glucocorticoid receptor; Hypothalamic–pituitary–adrenal axis

LDL cholesterol relates to depression, its severity, and the prospective course - Wagner, Claudia; Musenbichler, Cornelia; Böhm, Lea; Färber, Katharina; Fischer, Anna-Isabell; von Nippold, Felicitas; Winkelmann, Merle; Richter-Schmidinger, Tanja; Mühle, Christiane; Kornhuber, Johannes; Lenz, Bernd (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2019)
Background: Major depressive disorder (MDD) is a highly prevalent and burdening mental illness. Approximately 30% of the major depressive episodes (MDE) are classified as therapy-refractory. Further knowledge of the pathophysiological mechanisms underlying MDD and predictive biomarkers are needed to improve treatment options. Methods: Serum lipid levels were compared between patients with a current MDE (n = 130) or remitted MDD (n = 39) and healthy control subjects (n = 61) and associated with the severity (17-item Hamilton Depression Rating Scale [HAMD] scores) and the prospective course of depression (direct follow-up of at median 20 days post-inclusion). Results: We found higher levels of LDL cholesterol (152.5 vs. 134.0 mg/dl, U = 3021, P = 0.008) and LDL/HDL ratio (2.82 vs. 2.21, U = 2912, P = 0.003) in patients with a current MDE than in healthy control subjects. In patients with a current MDE, higher HAMD scores correlated also with higher values of triglycerides (ρ = 0.213, P = 0.015), total cholesterol (ρ = 0.199, P = 0.023), LDL cholesterol (ρ = 0.224, P = 0.010), and LDL/HDL ratio (ρ = 0.196, P = 0.026). Moreover, higher total cholesterol (ρ = −0.233, P = 0.010), LDL cholesterol (ρ = 0.235, P = 0.010), and LDL/HDL ratio (ρ = −0.199, P = 0.029) were associated with a stronger decline in HAMD score between study inclusion and direct follow-up. Limitations: We employed an associational study design, performed only a short-term follow-up, and excluded suicidal study subjects. Conclusions: Serum lipid levels are associated with depression per se, the depression severity, and the prospective 3-week course. These observations build the basis for future investigations on individualized lipid metabolism-related treatment strategies in depressed patients.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cholesterol; Depression; LDL cholesterol; Serum lipids; Triglycerides

Microsurgical treatment of cranial and spinal dural arteriovenous fistulas for acute occlusion: a single institution's experience - Winter, F.; Böhm, Lea; Shawarba, Julia; Callegari, K.; Buchfelder, Michael; Rössler, Karl (Neurological Research, 2022)
Objectives: To determine the success rate of primary microsurgical treatment of both cranial and spinal dural arteriovenous fistulas (cdAVFs and sdAVFs).
CRIS-Team WoS Importer:2022-08-26

Timing of sequential use of double-balloon catheter and oral misoprostol for induction of labor - Kehl, Sven; Böhm, Lea; Weiss, Christel; Heimrich, Jutta; Dammer, Ulf; Baier, Friederike; Suetterlin, Marc; Beckmann, Matthias; Faschingbauer, Florian (Journal of Obstetrics and Gynaecology Research, 2016)
AIM: The best time to commence cervical ripening with a balloon catheter is unknown. The aim of this study was to evaluate whether application of a balloon catheter in the morning or in the evening is better when sequential prostaglandin application is planned. METHODS: This multicenter historical cohort study included 415 women with an unfavorable cervix undergoing labor induction at term. Labor was induced with a double-balloon catheter and the sequential use of oral misoprostol if necessary. The balloon catheter was placed in the morning group between 02:00-15:00 and in the evening group between 15:00-02:00. The primary outcome measure was the cesarean section rate. Secondary outcome measures included failed labor induction (no vaginal delivery within 72 h). RESULTS: The cesarean section rate did not differ between the groups (morning 26.9%, evening 24.3%; P = 0.5553); however, more women in the morning group did not deliver within 72 h (8.8% vs 3.1%; P = 0.0138). In nulliparous women, labor induction failed more often in the morning group (12% vs. 4%, P = 0.043). In parous women, the induction-to-delivery interval was longer in the morning group (1756 vs. 1349 min; P = 0.046), and there were fewer deliveries within 24 h (35% vs. 56%, P = 0.016). CONCLUSIONS: When sequential use of a double-balloon catheter and oral misoprostol for labor induction is planned, the preferable time for catheter placement is in the evening. This resulted in fewer failed inductions in nulliparous women and a shorter induction-to-delivery interval and more deliveries within 24 h in parous women.
EVALuna2:32943